Information and treatment decision-making preferences of Filipino cancer patients in a government tertiary hospital - Yosuico, Victor Ernesto D.
Rationale: Disclosure of cancer as the diagnosis has been studies and deemed important by patients, their relatives and physicians. Little is known however, on what cancer patients' preferences are regarding their participation in decision-making and information needs regarding their disease, its prognosis and treatment options. It si generally assumed that Filipino patients rarely seek information regarding their disease, its prognosis and treatment, nor do they want to participate in decision making. However, no study has been done to systematically determine their real preferences. Objective: To determine the Filipino cancer patients' preferences for participation in treatment decision-making and for information. Design: Cross sectional analytic survey, using multiple card sort instrument to elicit information preferences and treatment decision-making preferences. Setting: Metropolitan tertiary training hospital (UP-PGH Medical Center). Methods: Sample size was calculated to estimate the true proportion of cancer patients who would want to make treatment decisions for themselves (p=.10, with 0.05 margin of error, 95% confidence interval, n=139). Multiple card sort instruments were used in the context of a face-to-face interview with a trained research assistant. Informed consent was obtained and confidentiality maintained. Sampling: Consecutrive cancer patients and their relatives (most responsible). Inclusion criteria: proven cancer diagnosis, ECOG 2 or better, literate, informed consent. Statistical Analysis: Descriptive statistics were used to described respondent characteristics. Thrustone scaling and ranking methods were used to determine the importance of information categories for patients and relatives. Distributions of the patients' overall information preferences and most highly preferred roles in treatment decision-making were compared using chi-sqaure in subsamples defined by sociodemographic, disease and treatment variables. Simple kappa coefficients for agreement (between cancer patients and their relatives assessment of their preferences) were calculated. Chi-square and Kruskall-Wallis tests were used to analyze data when applicable. Multinomial logistic regression analysis was done to determine possible predictor variables for information and treatment decision-making preferences. Results: A total of 201 cancer patients were included in the study. Information preferences data from 197 patients and treatment decision-making preferences data from 190 patients were obtained and analyzed. A set of 30 relatives was included in the study. Information preferences: Majority of the patient surveyed wanted to be informed about their disease (98% ;[ CI : 96-100] and about its treatment (99.5%; [95% CI : 99-100]). Quality of life and treatment options were the most important information categories for both patients and relatives. Twenty seven of 196 patients wanted to received only the information needed for self care (13.8%; [95% CI : 8.9-18.6]); another 13.8% wanted to received information only itf it is good news, while the majority wanted to receive all information, whether good or bad (72.4%; [95% CI: 66.1-78.8]). Treatment decision-making preferences. On the initial card sort, 136 of 190 patients chose authority as their preferred pattern of treatment decision-making (71.;6% [95% CI :65.1-78.1]), while 32 chose dependency (16.8%;[95% CI : 11.5-22.2]) and 22 chose autonomy (11.6%; 95% CI: 7.0-16.2]) as their preferred pattern of treatment decision-making. The treatment decision-making algorithms and car-sort instruments enabled the participants to reconsider and re-evaluate their initial choices and after going through the card-sorting process, most of the participants (108,56.8%) wanted a collaborative role with either both doctor and family (71,37.4%), with the doctor (25,13.2%) or with the family (12, 6.2%). A passive role was desired by 74 (38.9%) patients and the decision-making power was given to the doctor in 56 cases (29.5%), to the family in 7 cases (3.7%) or both the family and doctor in 11 cases (5.8%). After going through the card-sort instruments, only 8 (4.2%) of the 190 cancer patients preferred to have a truly autonomous role and to be the one responsible for making treatment decisions. More than half of the cancer patients interviewed (101, 53.2%) wanted to family to participate in the treatment decision-making, whether in a collaborative role (94,49.5%) or for the family to act as the main decision maker (7,3.7%). One hundred sixty-three (85.8%) of the 190 cancer patients acknomledged the role of the doctor in the treatment decision-nmaking process, whether in a collaborative role (107, 56.3%) or as the main player in treatment decision-making (56,29.5%). Relatives' assessment of preferences, The relatives were fairly in agreement with the preferences of their patients (kappa = 0.58). Conclusion: Filipino cancer patients seen in a government tertiary hospital want to be informed about their disease and its treatment. They also have preferences as to what information categories are important to them and as to the kind of information they would want to receive. The Filipino cancer patient apparently would want to participate in the treatment decision-making process; more than half would prefer playing an active, collaborative role. More than half would prefer that the family and the doctor play a collaborative role with the patient. Knowing that the majority of Filipino cancer patients involved in this study want to be informed and want to participate in treatment decision-making has implications on health policy, doctor and patient education, clinical practice and research.
Theses--((Master of Science in Epidemiology-Clinical Epidemiology) UPCM
Keywords: Cancer patient